A nonmonotonic modal authorization logic for pervasive computing. Issue 6 (8th July 2014) - Noorollahi, Ali; Fallah, Mehran S.
Abstract Modal logics have proven invaluable for authorization in distributed systems. The logics devised so far, however, are inadequate to meet the requirements of pervasive environments. Such environments are, in general, characterized as open systems in which computing and communication facilities are provided to human users in a dynamic manner. These features suggest the need for the modification of existing logics in two directions. First, users' capabilities being intrinsic to pervasive computing should be incorporated into the underlying modal logic. Second, the logic should be equipped with appropriate machinery so that it can deal with the imperfection in the information required for authorization. This paper has contributions in both directions. We present a logic that reflects how the capabilities of users change in different contexts. Nonmonotonicity is then added to the logic so that earlier decisions based on imperfect information can be retracted. The usefulness of our formulation is demonstrated through the added capacity it provides for specifying and enforcing access control policies in real‐life environments. We also present a minimal model semantics that reflects nonmonotonicity through the way it gives meaning to the formulas of the logic. Finally, we propose a sound and complete decision procedure based on semantic tableaux. Copyright © 2014 John Wiley & Sons, Ltd.